Development of psychophysical and technical and tactical potential of student martial arts athletes - Shchegolev V.A.; Sushchenko G.V.; Mihuta I.Yu.; Apchel V.Ya. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimentally substantiate the methodology for developing the psychophysical and technical-tactical potential of student martial arts athletes. Methods and structure of the study. The experiment, which was conducted at Peter the Great St. Petersburg Polytechnic University, involved 114 students involved in martial arts, who made up the control (CG) and experimental (EG) groups. During the study, an original methodology was developed aimed at improving the construction of movements through sensory-cognitive, motor-functional and motor-coordination components in the process of educational, training and competitive activities. Results and conclusions. It was found that classes according to the developed program made it possible to increase indicators in the EG, characterizing the level of development of mental (5.04-18.68%), physical (5.12-20.35%) and technical-tactical (12.38-21. 38%) of students' potential in comparison with indicators in the CG - mental (3.25-12.38%), physical (3.69-15.26%) and technical-tactical (7.25-12.38%) potential. Thus, the conditions for the development of psychophysical and technical-tactical potential among student martial artists during training sessions are: the use of special exercises in changing conditions with modeling situations of alternative uncertainty associated with varying the motor composition of response actions; reduction of time for solving a psychomotor task in a certain sequence (situation - attacking actions - defensive actions - plot of the fight - task being solved).